Information System for Services and Management of Fishermen's Data from the Kutai Kartanegara Marine and Fisheries Service - Annafi Franz; Budi Rachmadani; Fendi Fendi (TEPIAN, 2025)
This research generally discusses the service and data management in the Department of Marine Affairs and Fisheries who still store documents in hard files, This problem arises because the fisherman administration service at the Maritime Affairs and Fisheries Service is still using manual methods in managing data and data storage, causing data management and administrative services to take a slow time and sometimes the existing data is no longer accurate. From the needs of the community, they have a desire for these services to be fast, reliable, transparent, and trustworthy services. With the service information system and web-based data management, it makes it easier for the public and admins to access and find out fisherman data by accessing anywhere. The tool is used to describe the system model in the form of Entity Relationship Diagram (ERD). To implement the service information system and fisherman data management, supporting components are needed to work properly. The component uses Laravel framework programming and stores database in MySQL. The results of this research and application are expected to be able to overcome existing problems and be useful for those concerned.